PRELIMINARY STUDY OF WUCHERERIA BANCROFTI L3 LARVAE DETECTION IN CULEX QUINQUEFASCIATUS AS VECTOR POTENTIAL OF FILARIASIS IN ENDEMIC AREA OF SOUTH TANGERANG, BY UTILIZING PCR ASSAY FOR L3-ACTIVATED CUTICLIN TRANSCRIPT mRNA GENE AND TPH-1 GENE - Nasution, Silvia Fitrina; Adhiyanto, Chris; Indahwati, Evi (Indonesian Journal of Tropical and Infectious Disease, 2018)
South Tangerang district is an endemic area for Wuchereria bancrofti filariasis with a prevalence rate of microfilaria (mf) at a range of 1 - 2.4% in 2008-2009. Culex quinquefasciatus plays an important role as the major vector of transmission for the parasite. It remains a problem on how to determine that the mosquitoe roles as a vector or disease transmitter when there is no evidence of filarial parasite larvae 3 (L3) by the microscopic examination. In assessing the transmission risk of the filarial parasite, a DNA-based detection method was carried out to specifically detect the presence of W. bancrofti infective L3 larvae in the mosquitoe. The Polymerase Chain Reaction (PCR) was performed to detect a specific DNA obtained from W. bancrofti L3 larvae in a very low number or low antigen titer. The assay was purposed as preliminary study to detect the presence of L3 filarial of W.bancrofti in Cx. quinquefasciatus by utilizing the expression of L3-activated cuticlin transcript mRNA gene and tph-1 gene. The result of PCR based analysis of mosquitoes collected from the suggested area showed that there is a low but detectable number of L3 infected mosquito with W. bancrofti. Among the 18 isolated DNA samples of mosquitoes, we found 7 positive samples (38.89%) with the presence of filarial larvae DNA expressing L3-activated cuticlin transcript mRNA and tph-1 genes, which determined as 123 bp for Wb-cut-1.2 and 153bp for tph-1. In contrast by microscopic result, we found no evidence of L3 larvae of the parasite in the mosquitoe's dissecting samples. The PCR assay in our study was proven sensitive to detect the presence of Wb-L3 filarial larvae in Cx. quinquefasciatus